Effect of quality control circle activities on the blood pressure control rate in young and middle-aged hypertensive patients (品管圈活动改善中青年高血压患者血压达标率的效果分析) - QIU Tingting (邱婷婷); YE Liping (叶丽萍) (中西医结合护理)
Objective To investigate the effect of quality control circle (QCC) activities in improving the blood pressure control rate in young and middle-aged hypertensive patients in nursing clinics. Methods From July 1, 2020 to January 31, 2021, a total of 316 cases of young and middle-aged hypertensive patients were collected. According to the random number table method, they were randomly divided into control group and QCC group. Patients in the control group were given routine health education, and patients in the QCC group were given QCC activities on the basis of routine health education. A checklist for monitoring blood pressure was developed and factors influencing the successful blood pressure were analyzed. Countermeasures were carried out to improve quality of nursing interventions on hypertension. The two groups were intervened for 6 months, and the blood pressure control rate of the two groups was observed. Results Unreasonable lifestyle and lack of health education from nurses were the main risk factors for the blood pressure failure among young and middle-aged hypertension patients. The blood pressure control rate in the QCC group was higher than that in the control group(68. 35%, vs. 32. 91%, P＜0. 01). Conclusion QCC activities could improve the blood pressure control rate in young and middle-aged hypertensive patients. (目的 探讨高血压护理门诊中运用品管圈活动改善中青年高血压患者血压达标率的效果。方法 选取2020年7月—2021年1月高血压护理门诊中青年高血压患者316例, 根据随机数字表法随机分为常规组(n=158)和品管圈组(n=158)。常规组给予常规健康宣教, 品管圈组在常规组的基础上开展品管圈活动, 制定高血压患者血压达标情况督查表, 对影响达标的因素进行分析, 进而针对性制定对策以改进相关护理措施。两组分别干预6个月, 比较患者血压达标率情况。结果 生活方式不合理和护士健康宣教缺乏是中青年高血压患者血压不达标的主要危险因素。品管圈组患者血压达标率优于常规组(68. 35%vs. 32. 91%, P＜0. 01)。结论 开展品管圈活动能有效提高中青年高血压患者的血压达标率。)